The Influence of Emotional Intelligence on Student's Al- Qur'an Memorization Speed in MA Ponpes Al Iman Muntilan - Sarini; Imron; Mawardi, Imam (Urecol Journal. Part A: Education and Training, 2023)
Emotional intelligence is one of the factors that influences student learning outcomes. This study aims to determine the effect of emotional intelligence on the speed of the students in memorizing the Qur'an at the Al-Iman Muntilan Islamic Boarding School MA. This study uses a quantitative approach. Data collection techniques used were observation, interview, and questionnaire methods with simple random sampling techniques of 20 samples from 118 populations. Data analysis using simple linear regression. The results of this study indicate that the influence of emotional intelligence on the speed of memorizing the Qur'an of students is 42%, while the remaining 58% is influenced by other aspects that affect the speed of memorizing the Qur'an, such as the age factor of memorizing, memorizing methods, and so on. So it can be concluded that there is a significant influence of emotional intelligence on the speed of memorizing the Qur'an for students of MA Ponpes Al Iman Muntilan.